Modus of Girls Trafficking in Bongas Indramayu: Victimology Perspective - Hamja, Hamja; Sulistio, Faizin (Brawijaya Law Journal, 2021)
The Regency of Indramayu has been stigmatised as a land of trafficking of women and children, not only at national level, but it has also transcended overseas. This research is aimed to seek deeper into the perspective of the victims from Bongas, Indramayu regarding their involvement in the trafficking. This research employed case study method and field observation based on descriptive-analytical approach. This research reveals that the majority of the people in Indramayu are living in the breadline, and they are mostly poorly educated. Women in Indramayu are even denounced as the breadwinner, or locally called as “luruh duit” or rushing for money, and this term is inappropriately interpreted; women are burdened with the responsibility to raise the economic status of the families by working in big cities. The culture of earning money by migrating to big cities is seen as a chance for human trafficking. This research also suggests some strategies such as co-assisting and developing the program to identify, rehabilitate, and reintegrate the victims of the crime.